Adapting to Change: The Impact of Flexible Work Models On Employee Engagement and Retention “Proposing A Conceptual Model For Further Exploration - Khan, Azhar; Sethi, Sonia; Shad, Fazaila; Bibi, Maryam (2024)
This study reviews the literature to find relationships between flexible work arrangements, psychological empowerment, and employee engagement in modern organizations. With increasing flexible arrangements, there are pertinent questions on what such arrangements mean to the employees. The Justification of the study based on Social Exchange Theory caters towards examining how flexibility in working time, work-life balance, and a culture of trust translate into a sense of empowerment on the part of employees, inherently determining engagement. Adopting a quantitative research strategy, the research will develop a standardized questionnaire adapted from validated instruments. The targeted population will consist of employees in firms implementing flexible working arrangements determined with statistical formulas that provide assurance of sample size robustness. In evaluating the relationships among the variables and testing the proposed hypotheses, various advanced analytical techniques including Structural Equation Modeling (SEM) using Partial Least Squares (PLS), and SPSS will be applied. The findings are anticipated to demonstrate the empirical verification of flexible work arrangements impacting positively on psychological empowerment and employee engagement. This research serves to enhance the existing literature with more practical insights on how contemporary work arrangements raise employee satisfaction and retention levels. On the other hand, the implications of the study will reach academia and industry. Academically, the study will augment the knowledge pool of organizational behavior and human resource management while practically, it will guide organizations in formulating policies on flexible work that enhance committed productivity. Thus, the study will give a holistic overview of the dynamics between flexible work arrangements and employee engagement and provide meaningful insights for organizations in the transformation of work.